Preclinical data and early clinical experience supporting the use of histone deacetylase inhibitors in multiple myeloma - Richardson, P.G.; Mitsiades, C.S.; Laubach, J.P.; Hajek, R.; Spicka, I.; Dimopoulos, M.A.; Moreau, P.; Siegel, D.S.; Jagannath, S.; Anderson, K.C. (Leukemia Research, 2013)
Histone deacetylases (HDACs) mediate protein acetylation states, which in turn regulate normal cellular processes often dysregulated in cancer. These observations led to the development of HDAC inhibitors that target tumors through multiple effects on protein acetylation. Clinical evidence demonstrates that treatment with HDAC inhibitors (such as vorinostat, panobinostat, and romidepsin) in combination with other antimyeloma agents (such as proteasome inhibitors and immunomodulatory drugs) has promising antitumor activity in relapsed/refractory multiple myeloma patients. This mini-review highlights the role of protein acetylation in the development of cancers and the rationale for the use of HDAC inhibitors in this patient population. © 2013 Elsevier Ltd.
Keywords: bortezomib; Histone deacetylase; Histone deacetylase inhibitor; Immunomodulatory drug; multiple myeloma; proteasome inhibitor